A study on employees' commitment at Malaysian Palm Oil Board Sandakan / Nor Alina Atika Useh and Fareeza Abdul Firoz - Useh, Nor Alina Atika; Abdul Firoz, Fareeza (2016)
Malaysia Palm Oil Board (MPOB or LMSM) is the body that is responsible for planning, researching and developing palm oil industry and palm oil plantations in this country. MPOB are under that jurisdiction of the Ministry of Plantation Industries and Commodities. Malaysia Palm Oil Board established on 1 May 2000 the combined result Palm Oil Research Institute of Malaysian (PORIM) by Palm Oil Registration and Licensing Authority (PORLA). PORIM were created within early year 1979 below the Ministry of Primary Industry for devise and carrying out the examination associated with palm grease. PORLA on the other hand engaged in the marketing effort and palm oil guard. MPOB's Head Office is located at the Bandar Baru Bangi. Then the Licensing & Enforcement Division and Economics & Industry Development Division was centered in the Wisma Sawit at the Kelana Jaya Selangor. Meanwhile, the MPOB's Director General is the Datuk Dr. Choo Yuen May. This body has two types of employment status of workers which are permanent status and the status of contract workers. For the status of contract workers can be divided into two types of contract which are the "Board Contract" and the "NKEA's Contract". Board Contract is the contract under the Malaysian Palm Oil Board then the NKEA's Contract is the contract under the National Key Economic Area means that under the government project that based on the provided budget. The MPOB - Sandakan Port Station was started to operate in the year of 1989. There was 17 staff that on duty in the office. These 17 workers include the permanent and contract staff.